(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article aims to analyze the position occupied by actors and musicians in the production system of ancient Greek tragic spectacle, inside and outside the scene, in the interval between the 5th century BC and the 2nd century BC. For that, a trajectory was proposed that starts from tragedy as an activity limited to the families of the Athenian elite, passes through the emergence of a job market for actors, through the consolidation of a star system, until arriving at the organization of associations of artists of Dionysus. As representative of this path, the images of Sophocles, Kallipides, Neoptolemus and Kraton were evoked.